WHAT IS BEING DONE FOR A GENDER-FRIENDLY CAMPUS CLIMATE? UNITED STATES AND TURKEY AS A CASE - Belkıs, Özlem; Menteş, Ayşe Geysu (International Journal of Research -GRANTHAALAYAH, 2021)
Today, the process of learning is as important as the content of it as learning environments are part of the individual development. A gender-friendly campus climate that aims to create equal conditions for each student and aspires to prevent exclusion and marginalization caused by gender or sexual orientation is extremely important for the efficiency of education and individual development. Different organizations such as university administrations, feminist organizations, student and academic groups carry out various studies to constitute and maintain a gender-friendly campus climate. This article studies the collective implementations the US and Turkish Universities have been conducting to create a gender-friendly campus climate in the years of 2018 and 2019. At the end of the study, it is observed that the public sensitivity caused by adversity experienced by individuals has been an important aspect for the institutions to take action towards a gender-friendly campus climate. Moreover, research and studies of leading feminist academics have been an important fraction to guiding these steps. Also it has been enquired that ‘a standard implementation system to create a Gender-friendly campus climate’ cannot be the subject matter for every institution regardless of the country or location works in accordance within its own culture and structure.